The use of intersentence relational particles and asyndeton in First Peter - Janse, Van Rensburg J. J. (Neotestamentica, 1990)
This paper's discussion utilises the classification of meaningful relations between internuclear structures proposed by Nida, Louw, Snyman and Cronje in their book 'Style and discourse'; with special reference to the text of the Greek New Testamentand also the information in Domain 89 (Relations) of the Louw-Nida Lexicon, and Domain 91 (Discourse Markers).